(untitled) (Journal of Shaheed Suhrawardy Medical College, 2021)
Background: The management of high and complex anal fistulas remain a therapeutic challenge as it is often associated with recurrence and anal incontinence. The oldest and theoretically the simplest technique is to use a seton. The aim of this study is to find out the outcome of seton in the treatment of complex fistula in ano. Materials and methods: This cross-sectional study was done in surgical units of ShSMCH and colorectal surgery units of BSMMU from September 2014 to August 2015. Fifty patients with high anal fistula having internal opening above dentate line and with multiple fistulas tract were included by purposive sampling. Patients with low anal fistula, fistula in ano associated with Crohn’s disease, active abdominal tuberculosis, carcinoma of rectum, previous radiation therapy, with recurrent fistula in ano and in whom the internal opening could not be located were excluded. After initial evaluation, the fistula tract and opening were located. The skin and anoderm overlying the fistulous tract were incised. This double-strand seton was then tied over itself on the sphincter without excessive tension. The long end of each suture was tapped to the patient’s medial thigh. Postoperatively warm sitz bath after each bowel movement was advised. The patients were informed in detail about the presence of seton prosthesis and they were warned about the possible serous discharge that would continue until the seton dropped, and the wound healed. Data were recorded on the predesigned questionnaire and analyzed using SPSS version 16. Results: Among 50 cases mean age was 41 years, M: F was 4.5:1. Discharge from perianal sinus, pain, swelling and itching were common clinical presentation. All of the patients were discharged on the third postoperative day. None required readmission or needed narcotic analgesics after discharge. The average time for the seton to cut through the sphincter was 1 to 3 months. 28% had complete healing at 1 month and 66% at 3 months postoperatively. Flatus Incontinence was noted 16% cases followed by recurrence (6%), liquid stool incontinence (4%) and postoperative anal stricture was (2%) of cases. Conclusion: This study found that the seton is a safe and low morbidity option for the treatment of high and complex fistula-in-ano, having higher healing rates, with good quality of life. It can therefore be recommended as the standard treatment for complex fistula-in-ano. J Shaheed Suhrawardy Med Coll, December 2020, Vol.12(1); 15-19